Implementation and Preliminary Assessment of Workplace Post-Natal and Breastfeeding Support for Working Mothers - Francoise Cardoso; Erika Wasito; Tonny Sundjaya; Ray Wagiu Basrowi; Mikhael Yosia (ILUNI MKK FKUI and PRODI MKK FKUI, 2022)
Breastfeeding is undoubtedly the best nutrition for infants. Even throughout the COVID-19 pandemic, more pregnant mothers intend to breastfeed their babies. Despite this desire, not all of them succeed in initiating breastfeeding. One of the overlooked challenges in breastfeeding is that working mothers need to return to work, increasing hesitancy to continue breastfeeding due to numerous inconveniences, leading to full breastfeeding cessation. Systematic changes are needed following simple and practical changes: giving access to knowledge on breastfeeding while working, sharing advice and support from employers and colleagues, and providing a breastfeeding-friendly workplace, all of which can increase breastfeeding rates in many countries. Improvement in breastfeeding habits would also bring greater impact as increases in working mothers’ wellbeing will increase their work performance. Danone has done several breastfeeding initiatives and post-natal support in workplaces which has shown a positive impact through preliminary evaluation included in this study. The corporate world has not fully supported breastfeeding, but some best practices and learning points shed from this study could become an example that would lead to better commitments from other companies.